Oral Exposure to Chlorella sorokiniana Detoxifies Deoxynivalenol, Ochratoxin A, and Fumonisin B1 In Vitro and In Vivo - Hiroki Yamaguchi; Mana Ando; Chiharu Ohira; Tensei Magami; Mao Kaneki; Kazutoshi Sugita; Taro Ogawa; Ayaka Nakashima; Tomoki Fukuyama (Toxins)
Mycotoxins are synthesized by various fungal species and are known to exert toxic effects on vertebrates and other animals, even at low concentrations. However, the current countermeasure for mycotoxin contamination is random inspection of samples prior to shipment. In this study, we focused on Chlorella sorokiniana (CS) from Ishigaki Island, Japan, and examined its ability to detoxify deoxynivalenol (DON), ochratoxin A (OTA), and fumonisin B1 (FB1) in vitro and in vivo. The binding of CS to DON, OTA, and FB1 was evaluated in vitro. The detoxification of CS was demonstrated by monitoring its concentrations in the plasma and urine samples of male ICR mice. Plasma and urine samples were collected 30 min, 2 h, and 24 h after an oral administration of 5 mg/kg mycotoxins and/or 500 mg/kg CS. CS bound to more than 80% and 40% of DON and OTA, respectively, whereas the binding of CS to FB1 was less than 10%. The concentrations of DON and OTA in plasma and urine samples were substantially reduced by CS co-administration, whereas CS did not affect FB1 absorption. The co-administration of CS substantially inhibited the systemic absorption of DON and OTA.